Efecto de Acacia macracantha en las propiedades físicas y químicas del suelo en un sistema silvopastoril - Romero Delgado, Gelver (2021)
The aim of this study was to determine the effect of two ages of the long-spine acacia tree (Acacia macracantha) on the physical and chemical characteristics of the soil in a silvopastoral system with Guinea grass (Panicum maximum Jacq). The study was conducted in the Bellavista district, Cajamarca, Peru. The mechanical resistance, apparent density, humidity and temperature of the soil, as well as the content of organic matter, phosphorus (P2O5) and potassium (K2O) were evaluated in three soil locations: under the canopy of young (BCAj) and medium trees (BCAm) and outside the tree canopy (FCA), in two seasons of the year (dry and rainy). A complete randomized design with factorial arrangement 3 (location) x 2 (seasons) was used. Under the canopy of the medium trees, a lower soil temperature (27.96 °C) and higher soil humidity (15.23%) were found, in addition to improving soil fertility. The study made it possible to determine that the presence of trees in these silvopastoral systems improves the physical and chemical conditions of the soil, and generates a microclimate, improving environmental conditions.